Subterranean Electronic Blues; or, How a Former Technophobe Learned to Stop Worrying and Love... - Newell, Margaret E. (Journal of American History)
Presents information on the potential impact of information technology on academic historians. View that students may no longer be interested in the written word; Benefits of information technology; Background information on the author.